PERFORMANCE ANALYSIS OF PARKING SPACE CAPACITY AT DR. SOEDONO GENERAL HOSPITAL OF MADIUN - Labina, Bagastha Pudji Yurinko; Mudjanarko, Sri Wiwoho; Bahaswan, Rizal (Universitas Ibn Khaldun Bogor, 2022)
Parking is an element of facilities that cannot be separated from the overall transportation system. The increase in the population of a city will cause an increase in the need to carry out various activities. Hospital is one of the public facilities with a fairly high level of activity. However, in reality, the parking lot at the dr. Soedono General Hospital in Madiun is often full and disrupts the surrounding traffic. Therefore, it is necessary to analyze the performance of parking capacity and space at the dr. Soedono General Hospital. The research was done by doing a literature study on parking behavior, a preliminary survey at the study site, collecting primary and secondary data, then proceed with analyzing data in the form of capacity and parking space performance. The results of this study show that the maximum parking volume is 217 motorbikes/day and 249 cars/day, the average parking duration for motorbikes is 4.92 hours and 3.63 hours for cars, the maximum parking accumulation for motorbikes is 121 vehicles/day, and 62 cars/day, the maximum parking index for motorbikes and cars is 4.31% and 4.64%, and the parking space requirement for motorcycles (SRP) is 100 SRP and cars 80 SRP.